Pemanfaatan Interactive Flat Panel dalam Pembelajaran dan Dampaknya terhadap Kolaborasi Siswa di SD 1 Kemasan Boyolali - Muhammad Hafid Al Husain; Nunung Wulandari; Syamsul Huda Rohmadi (Instructional Development Journal, 2026)
This study aims to analyze the use of Interactive Flat Panels (IFPs) in instruction and their impact on student collaboration in elementary schools. This study employs a qualitative approach using a case study design at an elementary school that has implemented IFP. Data were collected through in-depth interviews with the Principal, sixth-grade teachers and students, non-participant observation, and documentation. Data analysis utilized the Miles, Huberman, and Saldana model, with triangulation techniques to ensure data validity. The results indicate that IFP is capable of transforming learning from passive to interactive and multisensory. IFP has also been shown to strengthen student collaboration through shared interactions, group discussions, and the emergence of spontaneous peer assistance. However, the use of IFP remains technical in nature and has not yet been optimally integrated into the collaborative learning model. There is a gap between school policies and implementation at the teacher level. Implications for practice: Structured teacher training based on the TPACK and SAMR frameworks is needed to optimize the use of IFP in collaborative learning. This study provides empirical evidence regarding the gap between policy and practice in the transformation of digital learning in elementary schools.